A novel sophisticated form of DMAS beamformer: Application to breast cancer detection. (April 2022) - Shah Karam, Seyyed Abbas; O'Loughlin, Declan; Asl, Babak Mohammadzadeh
Graphical abstract: Highlights: A more robust beamformer than the reference implementation of DAS and DMAS. The algorithm complexity is of a similar order to DAS. The DMAS-D4 achieves higher contrast and finer resolution. The improved performance is achieved with minimal additional computational load. The iterative implementation makes it suitable even for large MIMO imaging volumes. Abstract: Confocal microwave imaging (CMI) has the potential to be an alternative or complementary method for mammography in breast cancer screening. Data acquisition in CMI is very fast, safe, and comfortable for patients, but the reconstructed images are not always of high quality. High level of artifacts and poor resolution cause impaired quality. In this work, a novel, fast and robust beamformer, DMAS-D4 is presented. Delay-multiply-and-sum-degree-4 (DMAS-D4) is a next generation beamformer that expands the two-dimensional summations in delay-multiply-and-sum (DMAS) to four-dimensional summations in which all possible fourth degree terms are summed to increase robustness and resolution. A computationally-efficient implementation is presented which mitigates the additional computation required by DMAS. Furthermore, the proposed method can run iteratively which makes the ability to update the result using new observations. An idealized simulation compares basic performance of the proposed method with two other beamformers: (1) DAS, which is the gold standard, and (2) DMAS, which has been reported as the best beamformer so far. The results demonstrate that the DMAS-D4 achieves higher contrast and finer resolution. The proposed method increased the signal-to-max-ratio (SMXR) from 3.1 dB using DMAS to 5.7 dB in the heterogeneous breast mimicking phantom which illustrates the higher tumor detectability using the proposed method. Similarly, the Signal-to-Clutter Ratio (SCR) is 23.9 dB higher using the proposed method. By exploiting DMAS-D4 these benefits and potentially enhancing clinical decisions are attainable by the same computational load order as DAS. These results may be useful to inform future microwave breast imaging beamformer design.